The application of corneal collagen cross-linking in diseases other than keratoconus - Mrukwa-Kominek, Ewa; Drzyzga, Łukasz; Rogowska-Godela, Anna; Porwik, Ewa (Klinika Oczna / Acta Ophthalmologica Polonica, 2013)
Corneal collagen cross-linking is a method of treatment using ultraviolet radiation UVA and photosensitizing substance riboflavin to strengthen the chemical connections between the collagen fibers of corneal stroma. This treatment is focused on halting the progression of the diseases, called ectasias, characterized by irregular curvature and diminished thickness of the cornea. The most common indication for corneal collagen cross-linking is keratoconus. However, this technique may be also applied to pathologies other than keratoconus. The aim of this paper is to review the applicability of corneal collagen cross-linking in other conditions than keratoconus. Specifically, the conditions such as pellucid marginal degeneration, post refractive surgery ectasia as well as combined corneal collagen cross-linking and topography-based photorefractive keratectomy for topographies indicating forme fruste keratoconus are discussed. In addition, the effects of-corneal collagen cross-linking-as an adjunctive therapy in keratitis, corneal ulcers and corneal edema in bullous keratopathy are considered. The authors highlight the importance of treatment in clinical practice and the potential application of the treatment and modification of the protocols in the treatment of corneal diseases other than keratoconus.